Plan de negocio para la creación de una empresa consultora especializada en marketing para las pymes del cantón La Maná- provincia de Cotopaxi año 2015 - Olvera Alvarado, Darwin Darío (2016)
This research project: Business Plan for the creation of a consulting firm specializing in marketing for SMEs La Maná Cotopaxi Province 2015 "born of the need to contribute to the microenterprise sector of the canton; for the purpose of gathering information we proceeded to apply surveys business owners know which allowed the supply and demand for consulting services, as well as the percentage of acceptance of the proposal. The design of the business plan starts with the SWOT analysis of SMEs, which allowed to get strengths like being part of a large production unit; and also it became clear that most do not have a marketing plan established for their business....